Effect of Hydrophobicity on Frost Deposition on Vertical Cold Surfaces under Natural Convection Conditions - Zhao Lingqian; Liu Zhongliang; Li Liyan; Li Yanxia (Zhileng xuebao)
A series of visible frosting experiments on vertical superhydrophobic surfaces (153.2°) that were prepared by chemical etching and bare copper surfaces were conducted under natural convection conditions. The effect of hydrophobicity on the frosting process was investigated and compared under liquid nuclei and no-nuclei frost deposition mode. Furthermore, the effect of hydrophobicity on frost deposition was studied for cold surface temperatures (?50 to ?30 °C) and different air relative humidities (30%–70%). The experimental results showed that there was no liquid nucleation at the beginning of the experiment when the cold surface temperature was lower than ?30 °C at an ambient air temperature of 16 °C and a relative humidity between 30% and 70%. It was found that the frost crystals on the superhydrophobic surface were much denser compared than those on a copper surface under the no-nuclei frost deposition mode. This result was completely different from that of the liquid-nuclei frost deposition mode in which the frost formation on the superhydrophobic surface was suppressed significantly during the initial period of frost deposition. The frost crystal coverage of the cold surface was defined to characterize the density of the frost crystal distribution. It was revealed that as the relative humidity increased and the cold surface temperature decreased, the effects of hydrophobicity on frost deposition was mitigated, the frost crystal coverage difference between the superhydrophobic and plain copper surfaces was reduced, and the time during which the frost coverage difference lasted was shortened. The maximum frost coverage difference between the superhydrophobic and plain copper surfaces was greater than 15% and lasted for approximately 35 min in the case of cold surface temperatures ?30 °C, with the ambient air temperature at 16 °C and the relative humidity at 30%. The hydrophobicity had little effect on the frost deposition once the cold surface temperature was reduced to a sufficiently low temperature. The phenomena observed were also analyzed according to the theory of cloud physics and nucleation. It was found that the concave pits and the CuO crystal particles on the superhydrophobic surface provided advantageous sites for desublimation nucleation.